2022
DOI: 10.1111/imj.15855
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic demyelination syndrome: novel risk factors and proposed pathophysiology

Abstract: Background: Osmotic demyelination syndrome (ODS) is non-inflammatory demyelination in response to an osmotic challenge. It can be pontine or extrapontine in presentation.Aims: To retrospectively review cases involving ODS and define the spectrum of causes, risk factors, clinical and radiological presentations, and functional outcomes. Results:The study utilised data from 15 patients with a mean age of 53.6 years. Malnutrition (9; 60%) and chronic alcoholism (10; 66.7%) were the most common associated disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In over 75% of cases, ODS occurs after rapid correction of hyponatremia, and the mechanism is thought to be related to a relatively hypertonic insult [1,6]. Alcoholism, cirrhosis, malnutrition, and severe burns are some of the other conditions often accompanied by hyponatremia and have been described as risk factors for triggering ODS [1,7]. Our patient's history of alcoholism and HCV could have impacted her susceptibility.…”
Section: Discussionmentioning
confidence: 87%
“…In over 75% of cases, ODS occurs after rapid correction of hyponatremia, and the mechanism is thought to be related to a relatively hypertonic insult [1,6]. Alcoholism, cirrhosis, malnutrition, and severe burns are some of the other conditions often accompanied by hyponatremia and have been described as risk factors for triggering ODS [1,7]. Our patient's history of alcoholism and HCV could have impacted her susceptibility.…”
Section: Discussionmentioning
confidence: 87%
“…This condition is infrequently described and is associated with the presence of risk factors for this disease, for example, as alcohol use disorder and dysnatremia-causing pathology such as diabetes insipidus. Irregular treatment adherence was a relevant factor in this patient 2 13 14…”
Section: Discussionmentioning
confidence: 93%
“…Animal studies and case reports in humans have demonstrated that overcorrection of severe (<115 mEq/L) and chronic hyponatremia (>48 h) by >25 mEq/L can produce brain injury from cerebral demyelination [ 16 , 17 ]. There are numerous risk factors for developing demyelination, independent of the rate of correction, including severe liver disease, alcoholism, hypokalemia, hypophosphatemia, hypoxia, and malnutrition [ 18 ]. When demyelination occurs in high-risk patients, it can be difficult to ascertain what role the correction of hyponatremia played.…”
Section: Discussionmentioning
confidence: 99%